Factors of pet ownership associated with human health: A representative cross-sectional survey of Switzerland - Rahel Marti; Karin Hediger; Elena Pauli; Jan Hattendorf (PLoS ONE, 2026)
Background Studies have discussed the relation between pet ownership and several health outcomes, but the evidence remains inconclusive. It is suggested that factors related to the owner, the animal, and the human–animal relationship might explain general associations in findings. This study investigates differences in health, social support, life satisfaction, loneliness, and psychological well-being by pet ownership and regular animal contact status. It explores whether these outcomes are associated with attachment to the animal, perceived socio-emotional support from the animal, the animal species, and the amount of animal contact and how these variables relate to each other. Method We investigated data from a representative survey of 2,328 Swiss participants. We used health behaviour, health status, healthcare use, social support, life satisfaction, loneliness, and psychological well-being to conduct regression analyses, with pet ownership, human–animal contact, attachment to the animal, socio-emotional support from the animal, and the animal species as the predictors, while controlling for socio-demographic variables. Results Pet owners reported a slightly lower health status and a slightly higher frequency of unhealthy behaviour. We found no difference in healthcare use, loneliness, life satisfaction, psychological well-being, or the amount of human social support between pet owners and non-pet owners. People with regular animal contact did not differ in health status, health behaviour, healthcare use, loneliness, life satisfaction, psychological well-being, or human social support compared to people with no regular animal contact. Attachment to the animal and the animal species were not related to health, loneliness, life satisfaction, and psychological well-being, while socio-emotional support from the animal and the amount of animal contact were sometimes associated. Moreover, we found that attachment to and socio-emotional support from the animal were higher in females, in relation to dogs, and when people spent more time with the animal. Discussion We found little evidence for a general association between pet ownership or regular animal contact and human health and well-being. However, relationship-related factors, including socio-emotional support from the animal and the amount of contact with the animal, were sometimes associated with well-being. Moreover, the quality of the human–animal relationship depended on different factors, such as the amount of spent time with the animal or animal species. These findings suggest that associations between pet ownership and human health and well-being depend on characteristics of the owner, the animal and the human–animal relationship itself. Our study shows that pet ownership is a complex construct and should be conceptualised multidimensionally to understand its possible positive or negative associations with health outcomes.